El trabajo cooperativo como una estrategia lúdica para fortalecer la convivencia escolar (2021)
Cooperative work is a strategy in which students work as a team, establishing roles and agreements that enhance their individual learning by supporting each other, thus fortifying school coexistence, and strengthening bonds of respect and solidarity. Based on this concept, the project analyzes the problems presented in the Jacqueline Kennedy Educational Institution of the District of Santa Marta, particularly in the fifth graders, among whom problems of school coexistence are observed. Through this research, cooperative activities were developed as playful strategies to strengthen school coexistence in fifth graders, morning session of the IED Jacqueline Kennedy of the city of Santa Marta. This project was carried out through participatory action research, which allowed evidencing the impact of cooperative work in fifth grade students; for this purpose, it was developed in four phases (awareness phase, diagnostic phase, intervention phases and closing phase). Some workshops were held with the participation of teachers, parents and, of course, fifth grade students, which allowed to demonstrate the effectiveness of cooperative work as an agent that favors school coexistence, while students discovered skills that they did not recognize in themselves before.